Study of the effectiveness of technical analysis in foreign exchange trading - Lim, Wee Kian (2015)
This project studies the effectiveness of Technical Analysis in the foreign exchange market. The study used a single currency for its testing, namely the DM against US$ exchange rate. Testing is performed on an ex-post basis, using past exchange rate for the test. With numerous Technical Analysis models being available in the market, four more commonly used models are selected and their trading rules implemented in this study. They are the Single Moving Average, the Double Moving Average, the Momentum and the RSI. The study reveals evidence of profitability and accuracy of trading decisions made based on the trading rules. Certain models are found to be consistently profitable in the testing period while others are not. Although this definitely does not prove that Technical Analysis is effective as a whole, it does show that models of Technical Analysis with certain parameters produce better results than other parameters, take for example the 1 0 against 30 days Moving Average and the 4 days Momentum. Hence, the result suggests that the key to effective trading with Technical Analysis lies with selecting the appropriate model and using the right parameter when trading in a particular currency.